Mobile lab pack in teaching physics for secondary level, their academic performance and attitudes towards science - MABBAGU, NOREEN (Archīum Ateneo, 2019)
This study addresses the question of whether the Mobile Lab Pack in Teaching Physics is a better learning resource material to develop science process skills and increase the academic performance and attitudes towards Science through hands-on learning. It also sought to examine the possible relationship between academic performance and attitude towards Science of secondary level students. The Analysis, Design, Develop, Implementation, and Evaluation Model, known as ADDIE, a model of Instructional Design was employed in the development of the learning resources and materials. The study was conducted with two groups of Grade 7 students, each group with 40 samples. Four assessments tools were administered in the conduct of the study: a teacher-made Science Achievement and Process Skills Test comprising of 45 items was used for academic performances; Colorado Learning Attitudes in Science Survey (CLASS) for the assessment of attitude toward Sciences; Survey Questionnaire for Process Skills for process skills assessments, and Evaluation Checklist for P6-MOLAB in evaluating the learning resources and materials. The study found that Mobile Lab Pack in Teaching Physics could be a better learning resource material for Grade 7 Physics in the teaching and learning of Physics topics such as motion, heat, light as a wave, sounds, and electricity. The results have shown that applying ADDIE Model of instructional design in providing learning materials for hands-on learning could increase students academic performance and attitude towards science. The study also found that there is significant relationship between academic performance and attitude and that physics mobile lab is a potential learning resource material in understanding Physics.